Comparative evaluation of emissions and costs in renewable fuel production - Alexander Schneider; Moritz Harnischmacher; Andreas Rudi; Frank Schultmann (Journal of Business Economics, 2026)
In terms of cross-sectoral defossilization, Power-to-X processes seem promising by utilizing renewable electricity to produce sustainable energy carriers. However, their widespread adoption is hindered by technological, economic and environmental uncertainties. This study addresses these uncertainties by analyzing the production of regenerative fuels via Fischer-Tropsch (FT) and Methanol-to-Gasoline (M2G) syntheses. By integrating multiple scenario-based configurations of supply chains—ranging from electricity generation sources (grid, wind, photovoltaic (PV)) to hydrogen production technologies (alkaline, proton exchange membrane, and solid oxide electrolysis), heat supply options (natural gas, heat pump, process heat), and carbon capture methods (point source and direct air capture)—a comprehensive comparative economic and environmental life cycle analysis of renewable fuel production pathways is presented. The results suggests that supply chains incorporating alkaline electrolyser, point source carbon capture and heat pump in conjunction with an import strategy for intermediates produced with high renewable energy capacity factors appears to be the most promising. Trade-offs can be observed between M2G and FT as well as for PV and wind, wherein FT and PV show lower cost and M2G and wind show less emissions. In addition, the study highlights that decision-making on supply chain configuration is highly sensitive to regional aspects like infrastructure and resource availabilities (renewables, CO2), geopolitical and legal conditions. This poses a challenge not only in terms of establishing resilient supply chains, but also in terms of monitoring the various stakeholders along the entire value chain for the purposes of traceability and sustainability reporting.
Keywords: D24; P18; Q01; 650; Green hydrogen; Synthetic energy carriers; Power-to-X (P2X); Life cycle costing (LCC); Life cycle assessment (LCA); Industrial defossilization